Prognostic impact of epidermal growth factor receptor (EGFR) expression on loco-regional recurrence after preoperative radiotherapy in rectal cancer - Ychou Marc; Rouanet Philippe; Lemanski Claire; Zouhair Abderrahim; Barbier Nicolas; Bibeau Frederic; Azria David; Senesse Pierre; Ozsahin Mahmut; Pèlegrin André; Dubois Jean-Bernard; Thèzenas Simon (BMC Cancer, 2005)
Abstract Background Epidermal growth factor receptor (EGFR) represents a major target for current radiosensitizing strategies. We wished to ascertain whether a correlation exists between the expression of EGFR and treatment outcome in a group of patients with rectal adenocarcinoma who had undergone preoperative radiotherapy (RT). Methods Within a six-year period, 138 patients underwent preoperative radiotherapy and curative surgery for rectal cancer (UICC stages II-III) at our institute. Among them, 77 pretherapeutic tumor biopsies were available for semi-quantitative immunohistochemical investigation evaluating the intensity and the number (extent) of tumor stained cells. Statistical analyses included Cox regression for calculating risk ratios of survival endpoints and logistic regression for determining odds ratios for the development of loco-regional recurrences. Results Median age was 64 years (range: 30–88). Initial staging showed 75% and 25% stage II and III tumors, respectively. RT consisted of 44-Gy pelvic irradiation in 2-Gy fractions using 18-MV photons. In 25 very low-rectal-cancer patients the primary tumor received a boost dose of up to 16 Gy for a sphincter-preservation approach. Concomitant chemotherapy was used in 17% of the cases. All patients underwent complete total mesorectal resection. Positive staining (EGFR+) was observed in 43 patients (56%). Median follow-up was 36 months (range: 6–86). Locoregional recurrence rates were 7 and 20% for EGFR extent inferior and superior to 25%, respectively. The corresponding locoregional recurrence-free survival rate at two years was 94% (95% confidence interval, CI, 92–98%) and 84% (CI 95%, 58–95%), respectively (P = 0.06). Multivariate analyses showed a significant correlation between the rate of loco-regional recurrence and three parameters: EGFR extent superior to 25% (hazard ratio = 7.18, CI 95%, 1.17–46, P = 0.037), rectal resection with microscopic residue (hazard ratio = 6.92, CI 95%, 1.18–40.41, P = 0.032), and a total dose of 44 Gy (hazard ratio = 5.78, CI 95%, 1.04–32.05, P = 0.045). Conclusion EGFR expression impacts on loco-regional recurrence. Knowledge of expression of EGFR in rectal cancer could contribute to the identification of patients with an increased risk of recurrences, and to the prediction of prognosis.